Boarding School Management Strategies in Developing Student Character at State Islamic Senior High School (MAN) 2 Tanjung Pura - Cindi Gemilang; Amiruddin Siahaan; Fatkhur Rohman (Journal of General Education and Humanities, 2025)
This study analyses the boarding school management strategy in developing student character at State Islamic Senior High School (MAN) 2 Tanjung Pura. Character education is a crucial response to globalisation's moral crisis and challenges. In Islamic education, the boarding school system is a strategic platform for consistently and sustainably nurturing moral and spiritual values. The research collected data through observation, interviews, and documentation using a descriptive qualitative approach. A total of 32 students and 15 staff members participated in the study. Data were analysed through data reduction, presentation, and conclusion drawing stages. The findings reveal that character development is carried out through empathetic parenting, exemplary behaviour from teachers and caregivers, and senior student mentoring programs. Students and staff reported that these strategies foster discipline, independence, and responsibility. Supporting factors include consistent role modelling and structured daily routines in the dormitory. However, challenges such as the adjustment period for new students and a shortage of mentors still exist. This study supports the idea that Islamic boarding schools' humanistic and participatory management strategy creates a positive educational environment that encourages holistic character formation. These results are in line with previous research by Hasan (2021), Suryani (2020), Ma’arif (2019), Zuhri (2018), and Fadhilah (2017), who also found that well-managed dormitory systems significantly influence student moral development.